Isolation and identification of symbiotic fungi in roots of young Quercus mongolica on Liupan Mountain - DENG Xiaojuan1,2, LI Minqi1,2, LIU Jianli1, REN Yufeng1, ZHOU Libiao1, YAN Xingfu1,2* (Guangxi Zhiwu)
In order to elucidate community structures and dynamic changes of culturable symbiotic fungal colony in roots of Quercus mongolica, the symbiotic fungi in roots of young Q. mongolica at different ages were isolated directly. The isolated fungi were identified based on the morphological characteristics of colony and molecular analysis. The results were as follows:(1)A total of 249 fungal strains were isolated from the roots of young Q. mongolica, 18 species belonging to 15 genera, 8 families, 7 orders, 5 classes and 2 phyla were recognized. Among them, two species belonged to Basidiomycetes and 16 species belonged to Ascomycota. Pezicula pruinosa was the species with the highest isolation frequency(81.93%), followed by Dactylonectria torresensis (4.02%), Ilyonectria robusta (2.01%) and Atrocalyx nordicus (2.01%).(2)Significant differences in species and quantities of symbiotic fungi demonstrated in different ages of young Quercus mongolica, with the highest frequency of isolation occurring in the 4-5 years old(44.98%)followed by the triennial(29.32%), biennial(19.68%)and annual(6.02%). To sum up, culturable symbiotic fungi in the roots of young Q. mongolica on Liupan Mountain are highly diverse. Species and quantities of isolates vary at different ages of trees, the diversity increases with the growth of tree, and Pezicula pruinosa is the most dominant culturable symbiotic fungi in roots of young Quercus mongolica. The results provide the reference for further investigating symbiotic fungal resources and exploring the microbial symbiotic mechanism of Q. mongolica in adapting to local environment.